A New edition of Venantius Fortunas: The art of Criticism - Gillian Knight (Exemplaria Classica, 2021)
This edition forms part of the Cambridge Classical Texts and Commentaries Series.  As such it represents an important and scholarly contribution to a growing body of work on the poetry of late antiquity in general and Venantius Fortunatus in particular.  In addition to its technical treatment of metrics and textual tradition the introduction offers a helpful discussion of the generic background and of Fortunatus’ relationship to his sources and predecessors.  The erudite playfulness of these passages serves both to stamp Fortunatus’ individuality on the Vita and to bridge the gap with the inventiveness of his lyric output as revealed in the Carmina.[1]  Notwithstanding the caveats expressed earlier, Kay’s edition is to be hailed as a major piece of scholarship and to be celebrated for the richness of its commentary and the accessibility of its translation alike.  It is to be hoped that Books 3 and 4 will follow in the not too distant future.[1]  Roberts comments that the poem’s “wit” foreshadows medieval (and later) religious lyric (M. Roberts, “Venantius Fortunatus’s Life of Saint Martin”, Traditio 57, 2002, 129-187, 151), Quesnel that the poem unites “classicisme et esthétique baroque” (Quesnel, La Vie, LXIX).